Prospective Evaluation of Vacuum-Assisted therapy in patient with abdominal sepsis - Bilianskyi, L. S.; Prystaia, Y. V.; Tyshko, R. O.; Dubenko, Y. M.; Myroshnichenko, Y. Y. (Modern medical technology, 2019)
Purpose of the study. Improve treatment results of patients with abdominal sepsis, due to the diffuse acute secondary peritonitis, by choosing of the optimal method of laparostomy. Materials and methods. The analysis of treatment of 35 patients with common secondary peritonitis and abdominal sepsis accompanied by septic shock with score of the Mannheim Peritonitis Index 29, which were treated by laparostomy, during the period from 2014 to 2019, was performed. The patients were divided into 2 groups. The treatment group consists of 17 patients who were treated by negative pressure therapy (NPT) – a technique of vacuum-assisted closure of theabdominalcavity(VAC) withanegativepressure levels from 50 to 125 mm Hg in the continuous or intermittent modes. The control group consists of 18 patients, who were treated by laparostomy with planned abdominal sanations, with intervals between sanations of 24, 36, 48 hours, depending on the degree of development of peritonitis and the condition of the patient (as needed). Results. The average length of hospital stay in ICU department was 11,3 days in treatment group (from 5,2 to 16,4 days), compared with the control group 22,9 days (from 3,4 to 47,4 days). The number of relaparotomies during which the replacing or removing of VAC-bandages was performed at the end of NTP was 3,8 (from 1 to 4) in the treatment group and 6,8 (from 3 to 11) in the control group. Adequate source control of abdominal sepsis was achieved in all operated patients of the treatment group, and in the control group only in 7 patients (38,9%). The overall mortality rate in both groups was 20%. In the treatment group, which were treated by applying NTP 2 patients were died (11,8%) while in the control group this count was 27,8% (7 patients). Conclusion. The experience of applying NTP and VAC-bandages in the complex treatment of abdominal sepsis, with values of the SOFA 3, shows better results in comparison with other methods of open abdomen, reducing the length of stay in the ICU by 2 times, the mortality rate is 3 times and this allows to complete treatment with final closure of the abdominal cavity more than in 50% of patients.